The mRNA and protein datasets after cold stress of red tilapia - Lanmei Wang; Haoran Yang; Herbert Brightmore Munyaradzia; Wenbin Zhu; Zai-jie Dong (Scientific Data)
Abstract The cold stress during overwintering is considered the bottleneck of red tilapia industry. In this study, the water temperature (WT) was reduced by 2 °C per day from 20 °C to 8 °C in the cold (C) group. Then transcriptome of brain(B), gill(G), liver(L) and skin(S) tissues and proteome of G, L and S tissues were performed in C and Normal (N) (WT: 20 °C) group. 24 transcriptomes were completed, and 168.8 Gb data were obtained, with more than 5.89 Gb clean data of each sample. A total of 30499 annotation results were obtained with 3199, 4697, 4393, and 3382 differentially expressed mRNAs in NB_vs_CB, NG_vs_CG, NL_vs_CL, NS_vs_CS. 18 DIA proteomes were performed, and 6341 proteins were obtained with 178, 500 and 166 differentially expressed proteins in NG_vs_CG, NL_vs_CL, NS_vs_CS. Our datasets can be reused for key genes and proteins identification, omics joint analysis and regulatory mechanism analysis of low temperature or cold stress in fish, which will help understanding the regulatory mechanism and facilitate the molecular selective breeding of cold-resistant varieties of fish.